The benefit and risk of PD-1/PD-L1 inhibitors plus anti-angiogenic agents as second or later-line treatment for patients with advanced non-small-cell lung cancer: a systematic review and single-arm meta-analysis of prospective clinical trials - Chen, Shubin; Mo, Wanying; Jiang, Wei; Zhou, Shaozhang; Gan, Haijie; Yu, Qitao (Frontiers in Immunology, 2023)
1/PD-L1 inhibitors, anti-angiogenic agents, meta-analysis small cell lung cancer Methods: A single-arm meta-analysis was performed, and published literature from PubMed, Web of Science and Embase databases as of January 13, 2023, was systematically retrieved. We used the Cochrane risk of bias tool and methodological index for non-randomized studies (MINORS) Methodological items to evaluate the quality of eligible clinical trials. Outcomes including overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were extracted for further analysis. The random effect model is used to calculate the pooled parameters.Results: 19 studies (16 were non-comparative single-arm clinical trials and 3 were randomized controlled trials) were enrolled in this meta-analysis. In terms of tumor response, the pooled ORR and DCR were 22.4% (95% CI, 16.6-28.1%) and 76.8% (95% CI, 72.6-81.1%), respectively. With regard to survival analysis, the pooled PFS and OS were 5.20 (95% CI, 4.46-5.93) months and 14.09 (95% CI, 13.20-14.97) months, respectively. The pooled grade ≥3 adverse effect (AE) rate was 47.6% (95% CI, 33.1-62.0%) Conclusion: PD-1/PD-L1 inhibitors plus anti-angiogenic agents has promising efficacy and safety as second or later-line treatment in patients with advanced non-small cell lung cancer.